2018
DOI: 10.1111/dom.13233
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue lipid metabolism in morbid obesity: Effect of bariatric surgery‐induced weight loss

Abstract: A decrease in triglyceride content, coupled with the increased proportion of brown adipose tissue in the supraclavicular fat depot, may play a role in the improvement of whole-body insulin sensitivity observed in morbidly obese women after surgery-induced weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 40 publications
(97 reference statements)
4
34
0
Order By: Relevance
“…These characteristics make this tracer, when administered intravenously, an excellent method to measure tissue-specific plasma NEFA uptake rate, but not tissue oxidative or non-oxidative metabolism. Using 18 FTHA PET, BAT NEFA uptake was reported similar in healthy (~5.7 nmol.g −1 .min −1 ) and obese subjects (~3.9 nmol.g −1 .min −1 , non-significant vs. healthy) at room temperature (Figure 5 and Table 1 ), only slightly higher than the NEFA uptake rate observed in subcutaneous neck WAT (~4.7 and ~3.4 nmol.g −1 .min −1 , respectively) ( 114 ). In the later study, slight but significant increase in BAT NEFA uptake rate was shown 6 months after bariatric surgery in obese individuals (~5.0 nmol.g −1 .min −1 ) ( 114 ).…”
Section: Energy Substrates Utilization By Batsupporting
confidence: 67%
See 4 more Smart Citations
“…These characteristics make this tracer, when administered intravenously, an excellent method to measure tissue-specific plasma NEFA uptake rate, but not tissue oxidative or non-oxidative metabolism. Using 18 FTHA PET, BAT NEFA uptake was reported similar in healthy (~5.7 nmol.g −1 .min −1 ) and obese subjects (~3.9 nmol.g −1 .min −1 , non-significant vs. healthy) at room temperature (Figure 5 and Table 1 ), only slightly higher than the NEFA uptake rate observed in subcutaneous neck WAT (~4.7 and ~3.4 nmol.g −1 .min −1 , respectively) ( 114 ). In the later study, slight but significant increase in BAT NEFA uptake rate was shown 6 months after bariatric surgery in obese individuals (~5.0 nmol.g −1 .min −1 ) ( 114 ).…”
Section: Energy Substrates Utilization By Batsupporting
confidence: 67%
“…Using 18 FTHA PET, BAT NEFA uptake was reported similar in healthy (~5.7 nmol.g −1 .min −1 ) and obese subjects (~3.9 nmol.g −1 .min −1 , non-significant vs. healthy) at room temperature (Figure 5 and Table 1 ), only slightly higher than the NEFA uptake rate observed in subcutaneous neck WAT (~4.7 and ~3.4 nmol.g −1 .min −1 , respectively) ( 114 ). In the later study, slight but significant increase in BAT NEFA uptake rate was shown 6 months after bariatric surgery in obese individuals (~5.0 nmol.g −1 .min −1 ) ( 114 ). Interestingly, BAT NEFA uptake was inversely correlated with age, waist circumference and percent body fat and directly correlated with HDL cholesterol level ( 114 ).…”
Section: Energy Substrates Utilization By Batsupporting
confidence: 67%
See 3 more Smart Citations